Financial Company Decisions Using Social Media Content - Sutikno, Sutikno; Ramadani, Mery; Melyanti, Melyanti (Universitas Serang Raya, 2023)
Financial applications that make it easier for people to invest using technology. One of the efforts they can do is by looking for applications in the financial technology (FinTech) sector in the midst of developing technology in the internet of things (IoT) era. Company X is one of the FinTech sector companies that has an application to make interbank transfers free of admin fees and investment services. This application can help people manage finances, an issue that is being faced by millennials today about the tendency to use their money for entertainment rather than investment. This is also the basis for the company's decision to use their social media, by using content marketing strategies to attract the public. Content is created using message characteristics and builds brand awareness with excellence, can transfer between banks with free admin fees, and investment features easily and attractively for millennials. The method used is qualitative content analysis by looking at how much content is created through social media in responses. The results of this study show where the content marketing strategy carried out by financial company X on social media accounts, one of which is Instagram, provides characteristics built by companies that focus on educational, entertaining, persuasive characteristics that are packaged attractively for the millennial generation